2020
DOI: 10.17219/dmp/119743
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Knowledge, Attitudes and Practices of dental practitioners regarding the COVID-19 pandemic: A multinational study

Abstract: Background. Coronavirus Disease 2019 (COVID-19) has been declared a global public health emergency that is affecting people across the globe.Objectives. The aim of this study was to assess the Knowledge, Attitudes and Practices (KAP) of dental practitioners regarding the Coronavirus Disease 2019 (COVID-2019) pandemic.Material and methods. An online questionnaire was distributed among dentists across the globe using a combination of convenience and snowball sampling. The questionnaire was divided into 4 section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
188
19
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(290 citation statements)
references
References 19 publications
(21 reference statements)
51
188
19
7
Order By: Relevance
“…This study nds that most dentists have a better knowledge score, which is like the ndings among the Indian, Jordanian and Saudi dentists (Gambhir et al 2020;Kamate et al 2020;Quadri et al 2020). Although knowledge about symptoms is high among Bangladeshi dentists, most of them gave fewer right answers regarding the chance of getting infected from animals, types of COVID-19 virus, and airborne nature of novel coronavirus.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This study nds that most dentists have a better knowledge score, which is like the ndings among the Indian, Jordanian and Saudi dentists (Gambhir et al 2020;Kamate et al 2020;Quadri et al 2020). Although knowledge about symptoms is high among Bangladeshi dentists, most of them gave fewer right answers regarding the chance of getting infected from animals, types of COVID-19 virus, and airborne nature of novel coronavirus.…”
Section: Discussionsupporting
confidence: 70%
“…The response rate was quite low, perhaps because dentists might feel reluctant to ll up the questionnaire because of COVID related stress or unwillingness to take part in research initiatives. The study ndings revealed that the majority of the dentists who took part in this study, completed an undergraduate degree and only 29.3% dentists completed the postgraduate education, this is lower than reported in a multi-country study where only 35% dental practitioners and in Jordan only 30.4% completed their postgraduate education (Khader et al 2020;Kamate et al 2020).…”
Section: Discussioncontrasting
confidence: 63%
“…The main source information for the participants was social media, followed by the Television, which is in line with the multinational study done in India (Kamate, et al 2020). But it is in contradict with a study done in Nigeria in which the main source of information was mass media (Olapegba et al, 2020).…”
Section: Discussionmentioning
confidence: 80%
“…Sociodemographic factors which were commonly associated with better health literacy included higher educational level (23, 26, 27, 33, 34, 36, 37, 39, 40, 42, 43, 45, 72-77, 80-82, 88, 89), increased age (23,26,30,37,40,43,48,50,63,65,72,74,75,78,84,85) and female gender (13,16,23,26,33,34,38,40,41,44,45,60,62,72,74,78,80,81,84,85,89). For health systems-based factors, increased experience in the healthcare system (48,56,63,76,77,89) and attendance in health education programs (28,33,58,60,71,<...>…”
Section: Determinants Of Health Literacymentioning
confidence: 99%